THE EFFECT OF FDI ON PRIVATE INVESTMENT IN THE SOUTHEAST REGION OF VIETNAM - Nguyễn Văn Bổn (Tạp chí Khoa học Đại học Đà Lạt)
The Southeast region of Vietnam is the most dynamic economic area of the country and contributes the most to state budget revenue. Every year, this area attracts a high volume of foreign direct investment (FDI) inflows with the establishment of more industrial zones, export processing zones, and high technology parks. Do FDI inflows into this area crowd out/in private investment? This study uses the general method of moments (GMM) Arellano-Bond estimator to empirically investigate the effect of FDI inflows on private investment in the Southeast region from 2005 to 2018. The FE-IV estimator is employed to check the robustness of the estimates. The results show that FDI inflows crowd in private investment in this area. In addition, inflation increases private investment but infrastructure decreases it. The findings in this study provide some crucial policy implications for local governments in the Southeast region to attract more FDI inflows and stimulate more private investment.